Refractory Trigeminal Neuralgia to Medical Treatment Resolved by Microvascular Decompression: A Case Report - Gean Erick da Rocha de Maria; Andrezza Aragão Alcântara; Joanna Trycia Magalhães Alexandre Lima; Sarah Rodrigues Basílio; Mirna Marques Bezerra Brayner; Lívia Maria Sales Pinto Fiamengui; Paulo Roberto Lacerda Leal; Hellíada Vasconcelos Chaves (Archives of Current Research International, 2025)
Objective: The purpose of the present study is to report a case of trigeminal neuralgia (TN) refractory to medication due to a rare double compression of the trigeminal nerve by the superior cerebellar artery and the transverse pontine vein, resolved with microvascular decompression (MVD). Case: A 64-year-old woman with right-side TN (V2–V3) had severe facial pain triggered by chewing and brushing the teeth unresponsive to carbamazepine, lamotrigine, and clonazepam. High-resolution MRI showed the double neurovascular compression (superior cerebellar artery and transverse pontine vein). MVD was performed via retrosigmoid approach allowing the visualization of the double neurovascular compression, which were both compressions grade 2. An autologous muscle graft (AMG) was used instead of Teflon. Discussion: Venous compression is underdiagnosed and may coexist with arterial. AMG reduces inflammatory risks and reduces the risk of Teflon stiffness, which could cause additional compression. Conclusion: The patient remained pain-free and medication-free..High-resolution MRI was essential for diagnosis and surgical planning. MVD with AMG was safe and effective, providing immediate and lasting symptom relief.